THE EFFECT OF THE CONCEPT MAPPING STRATEGY ON THE ACCURACY OF PERFORMANCE AND COGNITIVE ACHIEVEMENT OF SOME BADMINTON SKILLS FOR FEMALE STUDENTS - Shaker, Dr. Zainab Nadhem; Muhammad, Dr. Manaf Abdulaziz (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The research aimed to identify the effect of the concept mapping strategy on the accuracy of performance and cognitive achievement of some skills in badminton for female students. The scientists postulated that there is a positive impact of using the concept mapping strategy on the cognitive achievement of badminton for third-year female students of the Department of Physical Education and Sports Sciences - University of Kufa. The researchers identified the research population as the third-year female pupils from the for the academic year, University of Kufa, College of Education for Girls, Department of Physical Education and Sports Sciences 2023-2024, who numbered (32) students. Researchers follow experimental strategies to meet research needs. The researchers used a measure of cognitive achievement and performance accuracy tests. For badminton skills, the scientific foundations of the research tests were extracted and after using the statistical package and transcribing the research results, the researchers concluded that the percentage of performance accuracy and cognitive achievement in the post-test increased for the experimental group that used the concept mapping strategy compared to the control group that used the traditional curriculum followed by the teacher. The researchers recommend the necessity of using the concept mapping strategy in developing the skills taught in racket games or other games, whether at the same stage or other educational stages.